Coordination of leaf economics traits within the family of the world's fastest growing plants (Lemnaceae). (20th June 2021) - Ishizawa, Hidehiro; Onoda, Yusuke; Kitajima, Kaoru; Kuroda, Masashi; Inoue, Daisuke; Ike, Michihiko
Abstract: The duckweed family (Lemnaceae) is a group of free‐floating aquatic plants with bodies consisting of single floating fronds that multiply clonally. Although they are known to have the fastest relative growth rate (RGR) among higher plants, their functional trait coordination in relation to within‐family variation of RGR is poorly understood. We tested how duckweed species fit within the trait covariation patterns known as the world‐wide leaf economics spectrum (LES). To this end, several functional traits were evaluated for 15 duckweed species, and their covariation patterns were compared with those in the global database of plant functional traits. As a group, duckweeds exhibited the most acquisitive suite of traits, with extremely small leaf mass per area (LMA), short life span and high mass‐based photosynthetic rate ( A mass ). These LES traits showed a tight correlation with RGR, corroborating our hypothesis that acquisitive leaf resource economics underpins their extremely high RGR. However, unlike other higher plants, LMA showed weak association with leaf life span and A mass within duckweed family. We also found a unique positive correlation between duckweed LMA and area‐based photosynthetic rates, an indication that their LMA represents different functional significance compared to typical higher plants. Synthesis . Duckweeds, the world's fastest growing plants, mostly follow the world‐wide LES and locate at its extreme end. The slight deviation from the LES highlights that duckweeds experience some physical and chemical constraints not faced by other higher plants. Abstract : Duckweeds, the world's fastest growing plants, mostly follow the world‐wide leaf economics spectrum (LES) and locate at its extreme end. The slight deviation from the LES highlights that duckweeds experience some physical and chemical constraints not faced by other higher plants.